Eating and conserving bushmeat in Africa - Wilkie, D.S.; Wieland, M.; Boulet, H.; Le Bel, S.; Vliet, N. van; Cornelis, D.; BriacWarnon, V.; Nasi, Robert; Fa, J.E. (Wiley, 2016)
In Africa, overhunting of tropical wildlife for food remains an intractable issue. Donors and governments remain committed to invest in efforts to both conserve and allow the sustainable use of wildlife. Four principal barriers need to be overcome: (i) communities are not motivated to conserve wildlife long‐term because they have no formal rights to benefit from wildlife, or to exclude others from taking it on their land; (ii) multispecies harvests, typical of bushmeat hunting scenarios, place large‐bodied species at risk of extinction; (iii) wildlife production cannot expand, in the same way that livestock farming can, to meet the expected growth in consumer demand; and (iv) wildlife habitat is lost through conversion to agriculture, housing, transportation networks and extractive industries. In this review, we examine the actors involved in the use of wildlife as food and discuss the possible solutions required to address urban and rural bushmeat consumption. Interventions must tackle use and conservation of wildlife through the application of context‐relevant interventions in a variety of geographies across Africa. That said, for any bushmeat solution to work, there needs to be concurrent and comparable investment in strengthening the effectiveness of protected area management and enforcement of wildlife conservation laws.